Biomarkers for predicting nucleos(t)ide analogs discontinuation and hepatitis B virus recurrence after drug withdrawal in chronic hepatitis B patients. Issue 4 (21st February 2022) - Luo, Mengqi; Zhou, Bin; Hou, Jinlin; Jiang, Deke
Abstract: Aim: To summarize HBV‐related biomarkers predicting nucleos(t)ide analogs (NAs) discontinuation and hepatitis B virus (HBV) recurrence after drug withdrawal in chronic hepatitis B (CHB) patients, providing references for clinical medication, so as to manage CHB patients more scientifically. Methods: Related pieces of literature were retrieved in PubMed and the results were sorted out. We then analyzed and summarized these articles. Results: We found that HBV related biomarkers maybe could predict NAs withdrawal safely and the possibility of relapse after treatment cessation, including hepatitis B e antigen (HBeAg), hepatitis B surface antigen (HBsAg), HBV DNA, HBV RNA, pregenomic‐RNA (pgRNA), hepatitis B core‐related antigen (HBcrAg), hepatitis B core antibody (anti‐HBc), and models containing several indicators for predicting the effectiveness of treatment. Conclusions: HBV DNA, HBV RNA, pgRNA, HBcrAg, anti‐HBc, as well as the prediction models formed by several biomarkers could predict the safe discontinuation of NAs before HBsAg loss and recurrence.